The Influence of Self-Control on the Impact of Exposure to Violence among Youths. Issue 6 (18th August 2019) - Brown, Wyatt
ABSTRACT: This study examines the role of internal factors in the relationship between exposure to violence and antisocial behavior. Specifically, this study proposes that the impact of exposure to violence changes depending on internalized factors such as self-control. Individuals with high exposure to violence but greater levels of self-control may be less influenced by the impact of exposure to violence. Conversely, individuals with low levels of exposure to violence and lower levels of self-control may be more influenced by the impact of violence. The findings from this study suggest that there is some buffering effect on the impact of exposure to violence which may be explained by levels of self-control. This finding is consistent with prior research which finds that the impact of environmental factors on crime and analogous behaviors can be influenced by other personal traits. The results of this study provide researchers and practitioners with important information regarding the impact of exposure to violence on antisocial behavior and the influence self-control has on this relationship. Due to the complex nature of human behavior and the preciseness needed involved in developing treatment or diversion plans the relationship between environmental and internal factors should be better understood.